THE IMPACT OF ROAD INFRASTRUCTURE DEVELOPMENT POLICIES ON COMMUNITY QUALITY OF LIFE IN BATAM CITY - Bambang Santoso Haryono; Choirul Saleh; Hendrik Trilaksono (Cognitionis Civitatis et Politicae, 2025)
Road infrastructure is a fundamental driver of economic growth and improved quality of life, especially in rapidly developing urban areas. This study examines the impacts of road infrastructure policies in Batam City, a strategic industrial and trade center in Indonesia. Using a quantitative descriptive approach, the research analyzes the influence of road infrastructure improvements on local economic performance, social welfare, and environmental sustainability. Data were obtained from secondary sources, including government reports, statistical records, and academic literature. The findings reveal that enhanced road infrastructure significantly improves accessibility and mobility, fostering economic opportunities and better access to critical services such as healthcare and education. Furthermore, these improvements contribute to environmental sustainability by reducing traffic congestion and emissions. However, challenges such as land acquisition disputes, funding constraints, and project management inefficiencies remain obstacles to policy implementation. This study emphasizes the need for inclusive planning, robust governance, and active community engagement to maximize the benefits of infrastructure development. The recommendations provided aim to guide policymakers and serve as a reference for similar urban regions undergoing rapid development.